Depletion of IK causes mitotic arrest through aberrant regulation of mitotic kinases and phosphatases. Issue 17 (1st July 2014) - Lee, Sunyi; Han, Sora; Jeong, Ae Lee; Park, Jeong Su; Yang, Young
Abstract : IK is known to inhibit the expression of major histocompatibility complex (MHC) class II antigen, but other cellular functions of IK remain to be uncovered. In this study, IK depletion caused misalignment of chromosomes through an increase in Aurora A and PLK1 phosphorylation, which was mediated by a decrease in PP1 and PP2A activities. On the other hand, the treatment of a dual inhibitor against CDK and Aurora kinases overrode IK depletion‐induced mitotic arrest through the activation of phosphatase activity. These findings imply that IK is an essential protein for achieving correct mitotic progress through the regulation of mitotic kinases and phosphatases. Abstract : Depletion of IK shows severe defects in mitosis. Depletion of IK induces aberrant activation of mitotic kinases. Inhibition of CDK1 and Aurora kinases overrides IK depletion‐induced mitotic arrest without cell division. IK is required for achieving correct mitotic progress.